2007
DOI: 10.1002/elps.200600413
|View full text |Cite
|
Sign up to set email alerts
|

Sample stacking for the analysis of catechins by microemulsion EKC

Abstract: In this study, an on-line concentration method, ASEI (anion-selective exhaustive injection)-sweeping technology which was coupled with microemulsion EKC (MEEKC), was used to analyze and detect six catechins ((-)-epicatechin, (+)-catechin, (-)-epigallocatechin gallate, (-)-epicatechin gallate, (-)-epigallocatechin, and (-)-gallocatechin). In addition to the effects of the buffer pH and electrolyte concentration on stacking, the compositions of microemulsion (types of oil phase, and types and levels of cosurfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…For example, the best MEKC separation was obtained for the nine tested aromatic acids when a pH 2 phosphate solution (50 mM) composed of 40 mM SDS was used as running solution, but three aromatic acids, TPA, p-TA and 4-CBA, still had similar migration velocities (their resolutions were smaller than 0.5). So far, there had been some reports on the use of on-line sample concentration techniques in combination with MEKC or MEEKC for the analyses of acidic compounds [21][22][23][24], but no studies employing on-line concentration MEEKC analyses of the type of aromatic acid impurities mentioned in this study have been reported in the literature to date. Several studies on on-line concentration procedure coupled to MEEKC separation had been reported by our group in recent years [23][24][25], and these results indicated that sample stacking provided relatively high detection sensitivity for acid species such as phenolic acid.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, the best MEKC separation was obtained for the nine tested aromatic acids when a pH 2 phosphate solution (50 mM) composed of 40 mM SDS was used as running solution, but three aromatic acids, TPA, p-TA and 4-CBA, still had similar migration velocities (their resolutions were smaller than 0.5). So far, there had been some reports on the use of on-line sample concentration techniques in combination with MEKC or MEEKC for the analyses of acidic compounds [21][22][23][24], but no studies employing on-line concentration MEEKC analyses of the type of aromatic acid impurities mentioned in this study have been reported in the literature to date. Several studies on on-line concentration procedure coupled to MEEKC separation had been reported by our group in recent years [23][24][25], and these results indicated that sample stacking provided relatively high detection sensitivity for acid species such as phenolic acid.…”
Section: Introductionmentioning
confidence: 88%
“…So far, there had been some reports on the use of on-line sample concentration techniques in combination with MEKC or MEEKC for the analyses of acidic compounds [21][22][23][24], but no studies employing on-line concentration MEEKC analyses of the type of aromatic acid impurities mentioned in this study have been reported in the literature to date. Several studies on on-line concentration procedure coupled to MEEKC separation had been reported by our group in recent years [23][24][25], and these results indicated that sample stacking provided relatively high detection sensitivity for acid species such as phenolic acid. There was, however, little improvement for basic (or cation) species because they were likely to be partially adsorbed on the surface of capillary inner wall during the sample introduction (for example the sensitivity enhancement factor (SER) increased by 96 000-238 000-fold for phenolic acid compounds [23], and 180-540-fold for tobacco alkaloid cations [25]).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies had demonstrated that the stacking efficiency and the peak shapes markedly improved when a HCB zone was injected before the Milli-Q water plug [18,22,24,28], as a result of the different electric field strengths between the Milli-Q water plug and the HCB plug. The HCB was used to form a wall, thereby reducing the anionic analytes' velocities and resulting in the anions stacking in a narrow zone.…”
Section: Optimization Of the Hcb Plugmentioning
confidence: 98%
“…Later, Zhu et al [19] analyzed six flavonoids in Chinese herbal medicine, and an increase in sensitivity of 13 to 31-fold was found in terms of peak height, and the limits of detection (LODs) achieved for standards ranged between 2.4 and 12.8 ng mL -1 . The combination of ASEI-sweeping and microemulsion electrokinetic capillary chromatography (MEEKC) has also been explored to improve the sensitivity in CE [20][21][22].…”
Section: Introductionmentioning
confidence: 99%